Produção de nanopartículas de piocianina como cobertura antibiofilme fúngico - Silva, Jonas Emanuel Guimarães da (2019)
Pyocyanin is a pigment of bacterial origin, with concentration-dependent antibacterial and antifungal action. Therefore, this work aimed to produce, characterize and evaluate a covering containing piocyanin nanoparticles as an antibiofilm agent against fungal species isolated from a painted external wall. Initially, six fungi of five genera were isolated: Aspergillus, Penicillium, Fusarium, Trichoderma and Tricophyton. The Minimum Inhibitory Concentration (MIC) of piocyanin was known in Aspergillus niger and Penicillium sp. at 140 μg/mL. Nanoparticles with and without pyocyanin were prepared by the nanoprecipitation method. The systems were characterized as: pH, encapsulation efficiency, morphology, particle size, polydispersion and zeta potential. Antibiofilm activity was evaluated in dolomite specimens under conditions with and without immersion in Sabouraud-Dextrose 2% broth. Afterwards, the number of cells was estimated by multiple tube technique and by visual inspection. The formulations developed presented good morphological aspects. The characterization values were satisfactory ranging from 581.9 to 668.7 (size); 0.33 to 0.57 (polydispersion); -4.40 to -5.37 (zeta potential) and 6.15 to 6.24 (pH). The best result of encapsulation efficiency was 56%. In tests with immersed specimens, the fungal population reached values of ≈103-104 NMP / 100μL / cm2. In the non-immersed condition, a reduction in fungal colonization was observed in the specimens that had the coverage of pyocyanin nanoparticles compared to the control group. The results demonstrated the viability of the formulation in biotechnological terms. However, further studies are needed to optimize this coverage